Ethnobotany Study of Kelakai (Stenochlaena palustris Bedd) as an Endemic Fern at Central of Kalimantan - Zannah, Fathul; Amin, Mohamad; Suwono, Hadi; Lukiati, Betty (Proceeding International Conference on Global Resource Conservation, 2015)
This ethnobotany study of Kelakai (Stenochlaena palustris) analyzes the aspect of the relationship between plant and people, especially about the indigenous knowledge such as the benefit and how the use of this endemic fern. Methods included participant observation and semi structured interviews with a total of one hundred and ten participants were conducted in Palangkaraya, at Central of Kalimantan. The result shows that the Dayak ethnic society in Palangkaraya believe that Kelakai (Stenochlaena palustris) useful to increase milk production, increase hemoglobin, and as anti aging. Consequently, identifying this endemic fernâs benefit can help to preserve the local wisdom of Dayak ethnic group and natural plant conservation.Â Keywords: Central of Kalimantan; endemic fern; ethnobotany; Stenochlaena palustris